Retórica no discurso organizacional: constituição do ethos da organização a partir de notas oficiais sobre acidentes - Magalhães, Ana Lúcia (2010)
Discourse, beyond plain linguistic production, shows complexity of its own it is a privileged locus of subjective construction. This text analyzes. under a rhetorical perspective, an official statement of an accident with a mining company (Mineração Cataguases) waste dam and three statements by Air France in the aftermath of an airplane crash in 2009. Those notes are herein treated as pieces of organizational discourse. The objective here is to investigate how the subjectivity studies contribute to the constitution of corporate ethos and find in the process which rhetorical criteria make possible the interpretation of official statements on accidents as builders of organizational ethos. The hypothesis is the existence of a discourse strongly marked by arguments created as function of problematicity and accident seriousness. Such discourse deeply interposes itself within the consolidated corporate discourse in order to show strength and minimize possible negative points. The discourse present in accident statements seeks to enhance transparency. It therefore elaborates texts focused on facts and uses texts with journalistic character, supposed as essentially objective. Since image is founded not solely on facts but also on impressions and those depend on an audience, subjectivity should permeate that discourse. Within the mentioned context, subjectivity was identified and analyzed according to the concepts set forth by Kerbrat-Orecchioni (1997), as well as the contribution made to the construction of company image. The theoretical bases are provided by rhetorical studies by Aristotle, Perelman, Maingueneau and Meyer. Aristotle‟s conception of ethos is related to character and personality, whilst Meyer‟s dimensions of ethos is not limited to the orator but also to answers to questions raised